Pendampingan Pengembangan Modul Projek Penguatan Profil Pelajar Pancasila dan Pelaksanaannya di SMP Muhammadiyah 2 Kota Batu - Zaenab, Siti; Chamisijatin, Lise; Aldya, Riantina Fitra (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: The project to strengthen the Pancasila student profile (Projek Penguatan Profil Pelajar Pancasila, P5) is a project-based co-curricular activity designed to strengthen efforts to achieve competency and character in accordance with the Pancasila student profile which is prepared based on Graduate Competency Standards. In the 2022-2023 academic year, SMP Muhammadiyah 2 Batu has implemented P5 using modules that have been prepared by the government and modified according to school conditions. This is because schools have not been able to create their own P5 modules. This community service aims to provide assistance in the development of the project module for strengthening the profile of Pancasila students (P5) and its implementation at SMP Muhammadiyah 02 Batu City. Method: The methods in the research are: training planning, training implementation, programme implementation evaluation assistance, programme sustainability evaluation. Result: Teachers can use AI applications to create learning material products in the form of PowerPoint presentations, short stories, graphics, images and learning videos that support more interesting subject matter. Increased ability and skills in the use of information technology and web-based learning media for teachers to support the learning process, resulting in increased student participation and understanding of the material. Conclusion: From this research, it can be concluded that teachers are collaborating to be more innovative and adaptable to technological advances that affect education. This collaboration with artificial intelligence must, of course, be adapted to valid and up-to-date references according to the needs of the material.